Dimer/monomer status and in vivo function of salt‐bridge mutants of the plant UV‐B photoreceptor UVR8. (9th September 2016) - Heilmann, Monika; Velanis, Christos N.; Cloix, Catherine; Smith, Brian O.; Christie, John M.; Jenkins, Gareth I.
Summary: UV RESISTANCE LOCUS8 (UVR8) is a photoreceptor for ultraviolet‐B (UV‐B) light that initiates photomorphogenic responses in plants. UV‐B photoreception causes rapid dissociation of dimeric UVR8 into monomers that interact with CONSTITUTIVELY PHOTOMORPHOGENIC1 (COP1) to initiate signal transduction. Experiments with purified UVR8 show that the dimer is maintained by salt‐bridge interactions between specific charged amino acids across the dimer interface. However, little is known about the importance of these charged amino acids in determining dimer/monomer status and UVR8 function in plants. Here we evaluate the use of different methods to examine dimer/monomer status of UVR8 and show that mutations of several salt‐bridge amino acids affect dimer/monomer status, interaction with COP1 and photoreceptor function of UVR8 in vivo . In particular, the salt‐bridges formed between arginine 286 and aspartates 96 and 107 are key to dimer formation. Mutation of arginine 286 to alanine impairs dimer formation, interaction with COP1 and function in vivo, whereas mutation to lysine gives a weakened dimer that is functional in vivo, indicating the importance of the positive charge of the arginine/lysine residue for dimer formation. Notably, a UVR8 mutant in which aspartates 96 and 107 are conservatively mutated to asparagine is strongly impaired in dimer formation but mediates UV‐B responses in vivo with a similar dose–response relationship to wild‐type. The UV‐B responsiveness of this mutant does not correlate with dimer formation and monomerisation, indicating that monomeric UVR8 has the potential for UV‐B photoreception, initiating signal transduction and responses in plants. Significance Statement: The plant photoreceptor UVR8 mediates photomorphogenic responses to UV‐B. When the homo‐dimeric UVR8 protein absorbs UV‐B, interactions between charged amino acids that maintain the dimer structure are neutralized, causing monomerisation and initiating signal transduction. Here we determine the importance of specific charged amino acids in promoting dimer formation and photoreceptor function, but show that particular mutant proteins strongly impaired in dimerisation are still capable of mediating responses to UV‐B in vivo, indicating that monomeric UVR8 can be active in photoreception.